Crystal structures and magnetic properties of novel two-dimensional iron tellurides flakes - Yang, Jiefu (2019)
Since the discovery of intrinsic magnetism in VX2 (X=S, Se and Te), two-dimensional transitional-metal dichalcogenides (2D TMDs), with hexagonal lattices, have become the emerging 2D confined systems showing potential intrinsic magnetic properties at the limit of a few atoms thickness. Often these 2D lattices also form other types of symmetries, like tetragonal or orthorhombic, but they have not been extensively investigated, mainly because of thermodynamic instability during crystal growth. In this study, we showed polymorphically controlled growth of 2D iron-telluride crystals of either hexagonal FeTe2 or tetragonal FeTe by varying the typical growth parameter, the flow rate of hydrogen gas. In addition, we also explored the possibility of the existence of intrinsic magnetism in the two different lattice structures. Furthermore, we demonstrated the different magnetism manifested by the two crystals by means of various characterization techniques.